Analgesic activity study of Polygonum glabrum willd in rodents - Kiron S.S.; Nizar K.; Rajagopal P.L.; Saritha M.; Narayaswamy V.B. (My University, 2025)
Investigations of herbal medicines may provide a novel drug for the treatment of pain, without addiction liability and gastric discomfort caused by opioids and nonsteroidal anti-inflammatory agents respectively. In the current study, an aqueous extract of Polygonum glabrum (PG) was evaluated for its putative analgesic activity in rodents. Hence the effects of the PG extract were evaluated through validated animal models of pain including acetic acid-induced writhing test, tail flick latent period, hot plate reaction time and formalin-induced paw licking. Aspirin (25 mg/kg, I.P.), pentazocine (10 mg/kg, I.P.) and indomethacin (5 mg/kg, I.P.) were administered to rodents as reference drugs. PG extract at doses of 12.5, 25, 50 and 100 mg/kg, i.p administered 30 min before the study has significantly decreased the number of writhing in acetic acid-induced writhing test and significantly increased the latent period and reaction time in the tail flick latent period and hot plate reaction time in rodents respectively. In acetic acid-induced writhing test, analgesic effect at doses 25, 50 and 100 mg/kg of PG were more significant than aspirin. In tail flick latent period, the effect of doses 50 and 100 mg/kg of PG were more significant than pentazocine. The confirmation test for pre-clinical analgesic activity of PG has performed by formalin-induced paw licking in rats. The observed analgesic activities of PG are mediated by both central and peripheral mechanisms.